KAZUO ISHIGURO’S NEVER LET ME GO: AN ANALYSIS THROUGH THE LENS OF PLACE - Neog, Biswajit; Kashyap, Kakoli (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores Kazuo Ishiguro's Never Let Me Go through the lens of spatial theory, examining how the construction and perception of place shape the novel's exploration of identity, memory, and human relationships. Drawing on Yi-Fu Tuan's concepts of space and place and Edward Relph's theory of place authenticity, the study investigates how key locations—such as Hailsham, the Cottages, and the recovery centers—function as more than mere settings, instead serving as active participants in the characters' emotional and existential journeys. The paper argues that these spaces embody the tensions between belonging and alienation, safety and confinement, and the known and the unknowable. By analyzing how the characters' sense of self is tied to their spatial experiences, this study sheds light on the broader implications of place in the novel, particularly in relation to themes of societal control, personal agency, and the inevitability of loss. Ultimately, the research highlights Ishiguro's nuanced portrayal of place as a medium through which human connections and existential truths are both forged and fractured.